Business communication of drivers and barriers for climate change engagement by Top New Zealand, Australian and Global Fortune 500 Corporations - Thaker J (Public Relations Institute of Australia (PRIA))
A small number of corporations are responsible for two-thirds of historical global greenhouse gas (GHG) emissions. While many studies have evaluated business communication about climate change, they have several limitations, including an understudy of businesses outside the U.S. and Europe, and a lack of cross-country benchmarking. This study compares 30 of the largest New Zealand companies with top Australian and Fortune Global 500 businesses on communication of drivers and barriers related to climate change engagement. A quantitative analysis of 90 corporations’ latest reports finds that the most frequently reported drivers are external and internal stakeholders, regulatory concerns, and commitment to a low carbon economy. Few organisations report barriers such as economic growth, process and technology factors, and regulatory uncertainty. New Zealand companies lag behind Australian corporations who communicate equally as well as the top Global 500 on different dimensions of drivers and barriers for engagement. Factors driving business engagement with climate change and its implications on business communication, are highlighted.
Keywords: business communication; climate change; drivers; barriers; public relations; New Zealand; Australia; Fortune Global 500; 1503 Business and Management; 1505 Marketing; 2001 Communication and Media Studies